D-π-D type fluorescent compounds based on dehydroabietic acid triarylamine: Synthesis, photophysical properties and application as hole-transporting materials in perovskite solar cells. (August 2021) - Gao, Yanan; Dou, Liwei; Gao, Hong; Song, Jie; Shang, Shibin; Song, Zhanqian
Abstract: D-π-D hole-transporting materials have the potential to be excellent dopant-free hole-transporting materials (HTMs) for perovskite solar cells (PSCs) because of their tunable energy levels, high charge mobility, good solubility, and excellent film-forming properties. In this paper, two series of D-π-D type compounds, Series 1 (2TPA-CZ1~2TPA-CZ3) and Series 2 (2DTPA-CZ1~2DTPA-CZ3), were synthesized by linking a carbazole derivative (as a π-bridge) to triaryamine or dehydroabietic acid triarylamine groups (the donor groups) via C–C coupling reactions. The optical, electrochemical, thermal, and photovoltaic properties in PSCs of these compounds were fully investigated. The two series of compounds exhibit good ultraviolet absorption, fluorescence emission, and electrochemical and thermal properties. In addition, their highest occupied molecular orbital levels and energy gaps make them suitable for use as hole-transporting materials in PSCs. Among the PSCs developed, Device 1, based on 2TPA-CZ1, showed the best performance, with a power conversion efficiency (PCE) of 12.27%, a open circuit voltage (VOC ) of 1.13 V, a short-circuit photocurrent density (JSC ) of 15.10 mA cm −2, and a fill factor (FF) of 71.61%, which is comparable to that of a device based on the conventional hole-transporting material Spiro-OMeTAD. While the PCE of Devices 4–6 was lower than the PCE of Devices 1–3, Devices 4–6 exhibit better stability. This may be due to the higher Tg and better film-forming properties of compounds formed using the dehydroabietic acid skeleton. In additional, the introduction of alkyl groups on the carbazole moiety decreased the efficiency of the PSC devices. These results demonstrate that the 2TPA-CZ1 compounds are promising HTMs for PSC applications. Graphical abstract: Image 1 Highlights: Two series of D-π-D type compounds were synthesized by linking a carbazole derivative to triaryamine derivatives. The compounds exhibited good photoelectric properties, thermal properties and film-forming properties. The HOMO and LUMO energy levels of the compounds have been studied through experiments and theoretical calculations. Compound 2TPA-CZ1 as a hole-transporting material in PSCs showed excellent performance.